The Association Between Possible Stressors and Mood Outcomes in Older Residents of Long-Term Care Facilities - Angevaare, Milou J.; van Hout, Hein P. J.; Smalbrugge, Martin; Blankenstein, Annette H.; Hertogh, Cees M. P. M.; Twisk, Jos W. R.; Joling, Karlijn J. (Frontiers in Psychiatry, 2022)
Introduction Resilience incorporates the presence of a positive response to some type of stressor. To properly explore resilience, it is important to systematically identify relevant stressors. We aimed to identify (combinations of) stressors with the strongest relationship with observer-reported and self-reported mood outcomes in older residents of long-term care facilities (LTCFs) in The Netherlands. Materials and Methods We included 4,499 older (≥60) residents of 40 LTCFs who participated in the Dutch InterRAI-LTCF cohort between 2005 and 2018. The association of possible stressors (single stressors, number of stressors, and combinations of two stressors) in this population with observer-reported (Depression Rating Scale) and self-reported mood outcomes was analyzed using multilevel tobit models and logistic regressions. Results Major life stressor [“experiences that (threatened to) disrupt(ed) a person's daily routine and imposed some degree of readjustment”] and conflict with other care recipients and/or staff were most strongly associated with both mood outcomes. Furthermore, conflict was a particularly prevalent stressor (24%). Falls, fractures, and hospital visits were more weakly or not associated at all. Overall, the associations were similar for the mood outcomes based on observer-report and self-report, although there were some differences. Multiple stressors were more strongly associated with both mood outcomes than one stressor. Conclusion Major life stressor and conflict emerged as important stressors for resilience research within the psychological domain in LTCF residents. Further (longitudinal) research is necessary to determine the directionality and relevance of the strong association of conflict with mood for LTCF practice.